Pengaruh PBL Berbantuan Quizizz Dalam Pembelajaran PJDM Terhadap Kemampuan Berpikir Kritis Siswa SMK - Permatasari, Bernadeta Winda Putri; Muchsini, Binti (Politeknik Negeri Ambon, 2024)
This research aims to test the differences in the critical thinking abilities of students taught using problem-based learning with the help of Quizizz compared to students taught using problem-based learning in trading company accounting subjects. The population of this research was class XI Accounting and Finance at State Vocational Schools, 72 students using the Purposive Sampling technique. This research uses a quasi-experimental research approach. Student critical thinking data was obtained through a pretest and a posttest. The prerequisite tests used are the normality test and the homogeneity test. The data analysis techniques used are the independent t-test, paired sample t-test, and n-gain test. The results of the research show that there is an effect of the problem-based learning model with the help of Quizizz on students' critical thinking abilities at state vocational schools. Thus, it can be concluded that there is an effect of the problem-based learning model with the help of Quizizz on students' critical thinking abilities at state vocational schools. Keywords: Critical thinking, quizizz, problem based learning